Lifetime enhancement for clustering protocols in heterogeneous wireless sensor networks - Basim Abood; Yasser Kareem Al-Rikabi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, we propose a new clustering method called fuzzy stable election protocol (FSEP), which is capable to overcome the bottleneck problem and addressing the uneven energy consumption problem in heterogeneous WSNs. We also propose an energy-efficient routing method called particle swarm optimization routing method (PSORM) to find the optimal routing path for the heterogeneous WSNs. PSORM seeks to investigate the problems of balancing energy consumption and maximization of network lifetime. To demonstrate the effectiveness of FSEP-PSORM in terms of lessening end-to-end delay, balancing energy consumption, and maximization of heterogeneous network lifetime, we compare our method with three approaches namely, chessboard clustering approach, PEGASIS, and LEACH. Simulation results show that the network lifetime achieved by FSEP-PSORM could be increased by nearly 38%, 45%, and 60% more than that obtained by PEGASIS, LEACH and stable election protocol clustering (SEP), respectively.